EVALUATION OF OUTER CORE VISCOSITY INFLUENCE ON THE EARTH FORCED NUTATION - Lubkov, M. V. (Одеські астрономічні публікації, 2007)
On the base of the combined method, consisting of the Sasao, Okubo, Saito (1980) approach with the iteration procedure, allowing couple finite element method with the solution of the Laplace equation, it have evaluated the influence of outer core viscosity on the components of the earth forced nutation. It was derived, that outer core viscosity actually doesn’t have influence on the in phase nutation components, but this influence can reach some percents for out of phase nutation components, if we suggest the average value of the outer liquid core viscosity is the order of 1010 Pas.